2011
DOI: 10.1016/j.febslet.2011.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐interleukin‐6 receptor antibody, tocilizumab, for the treatment of autoimmune diseases

Abstract: Interleukin (IL)‐6 is a cytokine with multiple biological activities. It contributes to host defense against pathogens, whereas accelerated production of IL‐6 plays a significant pathological role in various diseases. Clinical trials have demonstrated the efficacy of tocilizumab, a humanized anti‐IL‐6 receptor antibody, for patients with rheumatoid arthritis, Castleman's disease or juvenile idiopathic arthritis, leading to approval of this innovative drug for the treatment of these diseases. Since IL‐6 has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 159 publications
1
94
3
4
Order By: Relevance
“…Therefore, in AE, fewer cycles of tocilizumab might substantively Data are reported as median (interquartile range) unless otherwise indicated *Corresponds to mRS at the time of tocilizumab initiation in the tocilizumab group, at initiation of additional rituximab for additional rituximab group, and at 1 month from the last rituximab therapy for observation group, respectively mRS: modified Rankin Scale, IQR: interquartile range, † p < 0.05 for tocilizumab group vs observation group ‡ p < 0.05 for additional rituximab group vs observation group § p < 0.05 for tocilizumab group vs additional rituximab group improve the long-term outcomes, and the clinical response to tocilizumab treatment can be detected at early phase and be maintained throughout long-term follow-up. We found that the frequency of infectious or infusionrelated complications of tocilizumab were low, which is comparable with a previous report [12]. However, 3 patients had a moderately severe reduction in absolute neutrophil count.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Therefore, in AE, fewer cycles of tocilizumab might substantively Data are reported as median (interquartile range) unless otherwise indicated *Corresponds to mRS at the time of tocilizumab initiation in the tocilizumab group, at initiation of additional rituximab for additional rituximab group, and at 1 month from the last rituximab therapy for observation group, respectively mRS: modified Rankin Scale, IQR: interquartile range, † p < 0.05 for tocilizumab group vs observation group ‡ p < 0.05 for additional rituximab group vs observation group § p < 0.05 for tocilizumab group vs additional rituximab group improve the long-term outcomes, and the clinical response to tocilizumab treatment can be detected at early phase and be maintained throughout long-term follow-up. We found that the frequency of infectious or infusionrelated complications of tocilizumab were low, which is comparable with a previous report [12]. However, 3 patients had a moderately severe reduction in absolute neutrophil count.…”
Section: Discussionsupporting
confidence: 79%
“…IL-6 inhibits regulatory T-cell differentiation, which is crucial in maintaining the balance against IL-17-producing T-helper cells in regulating autoimmune processes [14]. Furthermore, IL-6 stimulates the differentiation of CD8 + cytotoxic T cells, which promote excitotoxicity-induced neuronal damage [12,13]. Considering that rituximab does not affect cytokines or antibody-producing plasma cells, we suggest that tocilizumab could potentially represent a good strategy for AE with inadequate response to rituximab, by blocking IL-6 and thereby ameliorating autoimmune neuronal damage with multidirectional mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mAb tocilizumab, which is directed against the human IL-6R, is successfully used to treat rheumatoid arthritis and Still's disease. [16][17][18] However, some significant caveats remain. Besides its proinflammatory role, IL-6 signaling has also been shown to exert strong anti-inflammatory effects.…”
mentioning
confidence: 99%